Pola Komunikasi Perempuan Pesisir: Studi Etnografi Komunikasi - Nurhidayah, Yayah (Communicatus: Jurnal Ilmu komunikasi, 2017)
Communication is bound by culture. As culture differs from one another, the communication practices and behaviors of individuals cared for in different cultures will have different communication methods. The coastal women's community is a sub-culture of the Cirebon community, besides having unique and distinctive characteristics, they have an important role in helping to increase the economic income of the fishermen's family. The involvement of coastal women in the public sphere is increasingly expanding their interactions and social relations, both with people inside and with outsiders. The implication is that coastal women are faced with various challenges in interactions that require communication competencies. Lack of understanding of the culture of the participants involved in the interaction will give rise to social conflict: such as quarrels, hostilities, misunderstandings and prejudices. Komunikasi itu terikat oleh budaya. Sebagaimana budaya berbeda antara satu dengan lainnya, maka praktek dan perilaku komunikasi individu-individu yang diasuh dalam budaya berbeda akan memiliki cara-cara komunikasi yang berbeda. Komunitas perempuan pesisir merupakan sub-kultur dari masyarakat Cirebon, selain memiliki karakteristik yang unik dan khas, mereka memiliki peran penting dalam membantu menambah penghasilan ekonomi keluarga nelayan. Keterlibatan perempuan pesisir di ranah publik, makin memperluas interaksi dan relasi sosialnya, baik dengan orang dalam maupun dengan orang luar. Implikasinya, perempuan pesisir dihadapkan pada berbagai tantangan dalam interaksi yang membutuhkan kompetensi komunikasi. Kurangnya pemahaman tentang budaya dari peserta yang terlibat dalam interaksi, akan melahirkan konflik sosial: seperti terjadi pertengkaran, permusuhan, salah paham dan prasangka.